Special issue on External Quality Assessment in Laboratory Medicine: Current Challenges and Future Trends - Salle, Barbara De la; Meijer, Piet; Thomas, Annette; Simundic, Ana-Maria (Biochemia Medica, 2017)
Quality assurance in the modern clinical laboratory is evidenced through the complementary processes of internal quality control and external quality assessment, also known as proficiency testing. By these processes and the achievement of accreditation to international (e.g. ISO) standards, the laboratory is able to demonstrate its competence to the users of its services, i.e. the clinicians and the patients they care for, who have an expectation that the results of diagnostic testing and monitoring of treatment are correct, comparable and fit-for-purpose within the scope of the service, wherever they are performed.
©Copyright by Croatian Society of Medical Biochemistry and Laboratory Medicine. This is an Open Access article distributed under the terms of the Creative Commons Attribution Non-Commercial License (http://creativecommons.org/licenses/by-nc-nd/4.0/) which permits unrestricted non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited.
Keywords: External Quality Assessment in Laboratory Medicine; Clinical Laboratory; Analytical; Healthcare systems; Technology; Haematology